Óptima compensación de la potencia reactiva en redes de distribución eléctrica basado en SIMULATED ANNEALING - Rojas Gómez, Jorge Andrés (2017)
In this paper an analysis of the optimum location of reactive compensation elements in electrical distribution networks was developed using a mathematical model, which has the capacity to solve the problem of low voltage levels and large active power losses. Which proposed a methodology with the implementation of the Simulated Annealing algorithm, programmed in Matlab mathematical platform, this algorithm solved the location and optimal dimensioning of capacitor banks. This model considered both the technical and the economic aspects. For its implementation, the IEEE 30-bus system and the Matpower tool were used to run the power flow and obtain all the data from the initial system. On the other hand, the algorithm has the capacity to minimize the active power losses in the system, improving the voltage profiles and consequently the reliability of the system.